Pengaruh Model Pembelajaran Inkuiri Dan Gaya Kognitif Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 2 Palu - Rosdiana Rosdiana; Maxinus Djaeng; Baso Amri (Mitra Sains, 2015)
This study aims to explain the influence of models of inquiry learning and cognitive styles of students towards mathematics student learning achievements. This study is a quasi-experimental design with factorial 2 × 2. The independent variable in this study is the inquiry learning and direct instruction. Cognitive styles of students is divided into two parts, namely the cognitive style field independent (FI) and cognitive style field dependent (FD). The dependent variable is the result of students' mathematics learning. The instrument used was GEFT test used to determine students' prior learning styles koognitif implemented and achievement test used to measure the learning achievements of students after learning mathematics implemented. Samples were students of class VIII SMP Palu Negeri 2 theconsist of 48 students were taken by purposive sampling technique. Data were analyzed using ANOVA analysis of two-path. The results showed that (1) there is an interaction between the model and style koognitif inquiry learning on learning achievement outcomes of mathematics, (2) there is a difference between students' mathematics learning achievements by inquiry learning model and the learning achievements of students who received direct instruction on a group of students who have FI force, (3) there are differences in mathematics learning achievements of students who received the inquiry learning model and who received students learning directly to the student groups which share FD cognitive styles, (4) there are differences in mathematics learning outcomes of students between who have cognitive styles FI and students who have the cognitive styles of students who obtain the FD on inquiry learning, (5) there are differences in mathematics learning achievements students’, among students who have cognitive styles FI with students who have the cognitive style FD on students who received direct instruction.